Sustainable roadside management from an innovative approach to ecosystem services and bioenergy generation (2020)
Road infrastructure is a social, economic and political manifestation of a territory, correlated with the processes of transformation of the landscape, influencing the natural environment and social structures. Linked to the roads are the surfaces dedicated to the roadsides where ecosystems, communities, communication networks, landscape, transport, among others, interact. In countries such as England, Belgium and France, studies highlight roadsides as potential sites for biodiversity conservation, generating ecosystem services for flood reduction, pollutant retention, noise abatement, carbon sequestration and many more. The impacts of roads on ecosystems and landscapes are generally related to the fragmentation of ecosystems, proliferation of invasive and allergenic species, reduction of native biodiversity, alteration of the hydrological cycle, microclimatic changes, production of particulate matter, noise, water and soil pollution. Roadside management can become a critical aspect of mitigating such impacts, as maintenance activities such as tree and shrub pruning, grass cutting, cutting frequencies, handling of residual plant material is complex due to the demand for large amounts of economic, technical and logistical resources. Recent trends of roadside verge research allow to highlight the need to adopt a transdisciplinary and systemic approach concerning territorial studies. Furthermore, we must also remark that it is vital that sustainable management of roadside verges develops a strong multidimensional vision from ecological, social, economic, technological and political points of view. In that context, this work proposes an integrated sustainability analysis for roadside management from an innovative approach to ecosystem services and bioenergy generation. The method is development of the first’s stages of systems dynamics modelation.